Prediction of sediment transport rate in irrigation canals using modified Laursen methodology - Kodoatie, Robert J., author; Simons, Daryl B., author; Julien, Pierre Y., author; Albertson, Maurice L., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
An improved method for predicting sediment transport in alluvial channels has been developed based upon modifications of the Laursen (1958) equation and based upon a wide range of field data. The applicability of this new method was tested for irrigation canals. The following canals were selected for the study: ACOP in Pakistan, American canals, Canal del Dique, CHOP in West Pakistan, India canals, and the Rio Grande Conveyance Canal, which have a range of flow depth from 0.67 m to 5.13 m and width from 3.19 m to 140.21 m. Comparisons between computed results from the modified formula and field data verify that the new method can be utilized to compute total bed-material load in canals.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.